Physico-chemical and organkleptic properties of red beet juice purified by shungite - Melnyk, Lyudmila; Krivorotko, Volodimir; Melnyk, Zinoviy (My University, 2013)
Fresh red beet juice contains substances which coulddeteriorate its quality. Therefore, juice should be purifiedfirst. The promising method of purifying red beetjuice from unwanted impurities is using carbon-bearingadsorbent - shungite, uniqueness of which can beexplained by existence of fullerenes and nanotubes.The aim of this paper is to study how physico-chemicaland organoleptic properties of red beet juice changewhen processed by shungite. Проведено дослідження по відновленню адсорбційних властивостей природного мінерала шунгіта, який використано для очищення соку столового буряка від пектинових речовин при виробництві харчового барвника. Запропоновано два методи регенерації шунгіта із урахуванням економічної доцільності та наявності необхідного обладнання на консервних заводах. Встановлено раціональні параметри регенерації шунгіта.
Keywords: pectins; shungite; beet juice; adsorption treatment; пектини; шунгіт; сік столового буряка; адсорбційне очищення; кафедра процесів і апаратів харчових виробництв; кафедра теплоенергетики та холодильної техніки; кафедра теоретичної механіки та ресурсоощадних технологій